Mental Health First Aid Programme in Nepal - Jha, A; Kitchener, B A; Pradhan, P K; Shyangwa, P; Nakarmi, B (Journal of Nepal Health Research Council, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Mental Health First Aid is a relatively new concept conceived in Australia about 10 years ago and by 2010 it has spread to 15 other countries including Nepal. It is designed to deal with mental health emergencies as well as to help people with developing mental health problems to get to appropriate help before a crisis occurs. This programme was launched in Kathmandu by SAF-Nepal in November 2010 when the Australian experts ran a workshop for over 22 delegates from various mental health organisations. The MHFA Nepal course is being evaluated and adapted to suit Nepalese context. New conditions including hysteria and epilepsy have been added in the Nepalese version. The programme is expected to raise mental health awareness and reduce stigmatising attitudes amongst the selected members of the general public and health professionals. <span style="font-size: 11.0pt; line-height: 115%; font-family: ";Calibri";,";sans-serif";; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ";Times New Roman";; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Keywords: early intervention; mental health education; mental health first aid.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>